PENERAPAN STRATEGI SQ3R (SURVEY, QUESTION, READ, RECITE, REVIEW) DALAM MENIGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP ISLAM NURUL JADID PANGLEGUR TLANAKAN PAMEKASAN - Romlatul Hasanah; Uswatun Hasanah; Khoirun Nasihin; Hudaifi Hudaifi; Moh Hosen (Institut Kariman Wirayudha Sumenep, 2024)
Many things are done by teachers in providing motivation to their students so that students are more active in learning. This research is motivated by some students who are not enthusiastic, passive in class. In addition, some students are less interested in the learning materials being studied so there is no encouragement to carry out learning activities. In this study the author formulates the problem, namely: How is the effectiveness of implementing the SQ3R strategy (Survey, Question, Read, Recite, Review) in Increasing Student Learning Motivation in Islamic Religious Education Subjects at Nurul Jadid Panglegur Tlanakan Pamekasan Islamic Junior High School?, What are the supporting factors and inhibiting factors for implementing the SQ3R Strategy (Survey, Question, Read, Recite, Review) in Increasing Student Learning Motivation in Islamic Religious Education Subjects at Nurul Jadid Panglegur Tlanakan Pamekasan Islamic Junior High School?. This type of research uses a qualitative approach based on the results of the research obtained in the form of descriptive data. The data sources of this study are the principal, PAI subject teachers, and students. The data collection procedures used are observation, interviews, and documentation. Meanwhile, data analysis in this study uses data reduction, data presentation, and data verification. The results of the research conducted by the researcher show that the learning process using the SQ3R Strategy at SMP Islam Nurul Jadid Panglegur Tlanakan Pamekasan has been implemented well and the implementation of learning is carried out according to the needs of students. Meanwhile, supporting factors for the implementation of the SQ3R learning strategy are teaching staff, facilities and infrastructure, and student readiness in receiving learning. Meanwhile, inhibiting factors for the implementation of the SQ3R learning strategy are, lack of time, passive students and lack of enthusiasm.